Biomarkers for Malignant Potential in Vocal Fold Leukoplakia: A State of the Art Review. (29th September 2020) - Wan, Ping; Ongkasuwan, Julina; Martinez, Julian; Sandulache, Vlad; Deng, Defeng; Jiang, Jack; Sikora, Andrew; Altman, Kenneth W.
Abstract : Objective: To explore biomarkers that are candidates for understanding potential degeneration to malignancy of vocal fold leukoplakia (VFL), with the goal of guiding future diagnostic and treatment recommendations. Data Sources: PubMed and Medline search engines. Review Methods: A systematic review was conducted by searching the following key words: vocal fold or laryngeal, coupled with leukoplakia or dysplasia, and combined with the term prognostic markers . We collated the biomarkers and their significance, followed by observing the power of their evidence by assessing the quality of the studies according to guidelines of tumor marker prognostic studies (REMARK). Conclusions: Prognostic biomarkers in the 16 studies are generally divided into 3 categories according to their biological roles: proliferation (Ki‐67, CK‐1 RS14024 SNP), cell cycle control (P53, p16, cyclin D1, p57kip2, interleukin‐10 [IL‐10], miR‐10a, and miR‐34c), cell adhesion, and invasion (neutrophil‐to‐lymphocyte ratio, OPN/CD44v6 axis, MMP‐1, vascular endothelial growth factor A, MMP‐9, serpin peptidase inhibitor 1, plasminogen activator, CTNN/B1, β‐catenin, NANOG, HERG1). The prognostic use of these biomarkers is limited due to the variable methodologies, study design, assay methods, and statistical analysis performed. Implications for Practice: Prognostic factors in vocal fold leukoplakia have important clinical implications regarding the potential for malignant degeneration. Although further study is needed, the currently available evidence suggests that p53, p16, cyclin D1, IL‐10, NLR, OPN and CD44v6, CTNNB1, and CTTN and FAK might be of particular interest in determining prognosis of VFL as related to malignancy. Future, large, well‐designed, prospective studies are expected to determine the prognostic power of these biomarkers before their implementation in routine clinical practice.